Incidence of chronic rhinosinusitis in chronic headache: diagnostic criteria - Chandrashekar, Shilpa; S., Sandeep; Shivaram Shetty, T.; Balakrishna, Rakesh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2016)
Background: Chronic rhinosinusitis and vascular headache share similar signs and symptoms, which includes nasal symptoms, facial pain and headache. The aim of the study was to evaluate incidence of chronic rhinosinusitis in patient with vascular headache. Methods: A group of 100 patients aged between 25-45 who presented to our OPD with complaint of headache were included in our study. Patients were assessed with rhinosinusitis disability index (RSDI) for major and minor criteria of rhinosinusitis. Results: The criteria of the American Academy of Otolaryngology—Head and Neck Surgery were applied to diagnose 82 cases of headache attributed to chronic rhinosinusitis. Out of 100 subjects who were asked to fill the rhinosinusitis disability index 70 subjects (34 men and 36 female) had functional score (F) of 0- 45, physical score (P) of 0-35 and emotional score (E) of 0-25 and total score of 0-105, whereas 12 subjects (5 men and 7 female) had functional score (F) of 0-22, physical score (P) of 0-30 and emotional score (E) of 0-20 and a total score of 0-72. Conclusions: Out of total 100 patients with headache (62 men and 38 female), 82 subjects (54 male and 28 female) had chronic rhinosinusitis and 18 (10 men and 8 female) had vascular headache.